Regional Government’s Innovation in Sustainable Development-Based Garbage Management in Badung Regency - I Kadek Alit Manuartha; Abdullah Said; Wike Wike (Wacana Journal of Social and Humanity Studies, 2019)
Innovation in garbage management becomes one of the adaptation strategies which is responsive to the environmental pollution impact. Regional government’s innovation in garbage management is a city development concept which puts forward sustainable aspects. Sustainable development is a basic principle of garbage management concept, then it demands the presence of society’s participation and the other stakeholders. The research aims to describe and analyze the regional government’s innovation in sustainable development-based garbage management in Badung Regency. The research used descriptive research method with qualitative approach and qualitative data analysis of interactive model. The research results showed that the regional government in garbage management could be formed because the presence of motivation, skill, knowledge and conducive environment. The regional government’s innovation in garbage management was on generating possibilities. On the other hand, the facilities and infrastructure which were not optimal yet became the inhibiting factor of innovation.